NLRP3 Inflammasomes in Parkinson's disease and their Regulation by Parkin. (15th October 2020) - Yan, Yi-Qun; Fang, Yi; Zheng, Ran; Pu, Jia-Li; Zhang, Bao-Rong
Highlights: The role of NLRP3 inflammasome in Parkinson's disease pathogenesis. Parkin may regulate neuron inflammation in both mitochondria dependent and mitochondria independent manner. Targeting chronic inflammation is the future for Parkinson's disease treatment. Abstract: Chronic inflammation might correlate with the formation of α-synuclein oligomers, subsequently leading to dopaminergic (DA) neuronal death in Parkinson's disease (PD). As major components of chronic inflammation, NOD-like receptor protein 3 (NLRP3) inflammasomes play a crucial role in PD via caspase 1 activation, primarily induced by mitochondrial damage. NLRP3 binds to apoptosis-associated speck-like protein containing a CARD (PYCARD/ASC), and forms inflammasomes in the brain. Inflammasomes act as a platform for caspase 1 to induce interleukin 1 Beta (IL1β) maturation, leading to neuronal pyroptosis. Furthermore, alpha-synuclein, whose abnormal aggregation is the main pathogenesis of PD, also activates NLRP3 inflammasomes. Mutations to PRKN (encoding Parkin) are the most common cause of autosomal recessive familial and sporadic early-onset PD. Evidence has confirmed a relationship between Parkin and NLRP3 inflammasomes. In this review, we summarize the current understanding of NLRP3 inflammasomes and their role in PD progression, and discuss their regulation by Parkin.